The influence of lifestyle and financial literacy on online paylater system and its impact on spending behavior - Kamil, Islamiah; Ariani, Meiliyah; Irawan, Indra Ade (Journal of Economics and Business Letters, 2024)
This research aims to examine the influence of Lifestyle and Financial Literacy on the Paylater Online System and its impact on Spending Behavior. The analytical method used to test the hypothesis is path analysis. This research uses a sample of 200 respondents who are people who use the Online Paylater System in the Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) areas. In this research, sampling used convenience sampling. The research results show that the direct influence of Lifestyle and Financial Literacy on Spending Behavior shows significant results. However, the indirect effect for each independent variable is different. Lifestyle shows that there is an indirect influence through the Paylater Online System, while for Financial Literacy there is no indirect influence through the Paylater Online System. In theoretical contributions to the preliminary study, among others, Sari (2021) found that the ease of using Paylater technology by e-commerce users in Indonesia is very good and Paylater users tend to do impulse buying when shopping. It is hoped that this research can help the Online Paylater System in making decisions about spending its finances. Apart from that, Marketplaces that provide payments using the Online Paylater System are also expected to be able to maintain and increase the trust of their users.Future researchers should variableize other factors that influence the Online Paylater System and Spending Behavior, such as financial capability, risk and security, so that they can get more solid conclusions for the public regarding the Online Paylater System and changes in behavior or spending habits (Spending Behavior).